Olfactory dysfunction as an early pathogenic indicator in C. elegans models of Alzheimer's and polyglutamine diseases - Xue, Weikang; Lei, Ziyi; Liu, Bin; Guo, Hanxin; Yan, Weiyi; Jin, Youngnam N.; Yu, Yanxun V. (Frontiers in Aging Neuroscience, 2024)
Neurodegenerative diseases such as Alzheimer's disease and polyglutamine diseases are characterized by abnormal accumulation of misfolded proteins, leading to neuronal dysfunction and subsequent neuron death. However, there is a lack of studies that integrate molecular, morphological, and functional analyses in neurodegenerative models to fully characterize these time-dependent processes. In this study, we used C. elegans models expressing Aβ1-42 and polyglutamine to investigate early neuronal pathogenic features in olfactory neurons. Both models demonstrated significant reductions in odor sensitivity in AWB and AWC chemosensory neurons as early as day 1 of adulthood, while AWA chemosensory neurons showed no such decline, suggesting cell-typespecific early neuronal dysfunction. At the molecular level, Aβ1-42 or Q40 expression caused agedependent protein aggregation and morphological changes in neurons. By day 6, both models displayed prominent protein aggregates in neuronal cell bodies and neurites. Notably, AWB neurons in both models showed significantly shortened cilia and increased instances of enlarged cilia as early as day 1 of adulthood. Furthermore, AWC neurons expressing Aβ1-42 displayed calcium signaling defects, with significantly reduced responses to odor stimuli on day 1, further supporting early behavioral dysfunction. In contrast, AWA neuron did not exhibit reduced calcium responses, consistent with the absence of detectable decreases in olfactory sensitivity in these neurons. These findings suggest that decreased calcium signaling and dysfunction in specific sensory neuron subtypes are early indicators of neurodegeneration in C. elegans, occurring prior to the formation of visible protein aggregates. We found that the ER unfolded protein response (UPR) is significantly activated in worms expressing Aβ1-42. Activation of the AMPK pathway alleviates olfactory defects and reduces fibrillar Aβ in these worms. This study underscores the use of C. elegans olfactory neurons as a model to elucidate mechanisms of proteostasis in neurodegenerative diseases and highlights the importance of integrated approaches.